PERBEDAAN PENDAPATAN USAHA TANI JAMUR PADA KEMITRAAN DAN NONKEMITRAAN KOPERASI PRODUKSI JAMUR MEREKAH DAERAH ISTIMEWA YOGYAKARTA - Amin Wahyu Prasetyo; Nanang Kusuma Mawardi; Artita Devi Maharani (Fakultas Pertanian UST, 2025)
This study aims to analyze the differences in income of partner and non-partner farmers, as well as to analyze the influence of experience, income, farming costs, productivity, and partnerships on the income of mushroom farmers at the Koperasi Jamur Merekah. The research method is to use quantitative research with a sampling technique using purposive sampling. The number of samples used consisted of 20 partner farmers and 20 non-partner farmers. The analytical method used is multiple linear regression analysis and paired sample test. The results of multiple linear regression analysis show that there is a partially significant influence on the variables of experience, farming costs, and partnerships on the income of mushroom farmers, while productivity has no partial effect on the income of mushroom farmers at the Koperasi Jamur Merekah. Based on the results of the simultaneous hypothesis test (F test), it shows that simultaneously the independent variables (experience, farming costs, productivity and partnerships) have a significant effect on the income of mushroom farmers. Based on the results of the paired sample test, it shows that there is a difference in average income between partner and non-partner mushroom farmers, where the average income of partner farmers is higher than the income of non-partner farmers. Koperasi Jamur Merekah needs to provide guidance to farmers who have not yet partnered so that they can partner to increase their experience, knowledge and benefits to increase the income of their mushroom farming business. Keywords: Experience, Farming Costs, Productivity, Partnership, Income.